Workplace happiness in architectural companies in the city of Valencia: a gender comparison - Rodríguez-Leudo, Ana Lucía; Navarro-Astor, Elena (Frontiers in Sustainable Cities, 2024)
How to make work life increasingly meaningful and ensuring that business actions aim at improving quality of life and human development is still a trending topic. Yet, it has not often been studied within architectural firms, that play a crucial role in achieving sustainable development goals, especially those related to equity, equality, and the creation of pleasant work environments that enhance positive emotions. This study aims to identify whether there are gender differences in the perception and levels of workplace happiness of individuals working within architectural companies in Valencia (Spain). A mixed methodology based on qualitative and quantitative data has been applied with a sample of 201 workers from 60 practices. Participants perceive themselves as flourishing and quite happy at work. Yet, there are gender differences in the factors that motivate workplace happiness. While women prioritize the work environment, their colleagues and their team, men point out to career development. Thus, recognition, appreciation, feeling valued and goals and achievements are among the main drivers of men’s workplace happiness. In addition, women tend to experience negative emotions such as anxiety, anger, or sadness more frequently than men. Given these results, architectural companies face a considerable challenge.